Integrative and syntactic complexity’s role in decision-making under uncertainty - Castellón-Flores, Alejandra Mitzi; Molina-Perez, Edmundo; Molina, Isaac; Cortes, Pedro Manuel; Sobrino, Fernanda; Serra-Barragan, Luis (Frontiers in Psychology, 2025)
This study explores the impact of integrative complexity (IC) and syntactic complexity (SC) on decision-making under uncertainty. The research addresses how cognitive structures contribute to decision quality in ambiguous situations. A modified Ellsberg experiment was conducted using an online platform. Participants were exposed to varying levels of ambiguity, and decision support tools were introduced to assess the influence of IC and SC on decision-making. The manipulation of available information allowed for a controlled analysis of cognitive processing. The findings reveal that IC and SC significantly enhance decision quality. IC facilitates the integration of diverse information, while SC supports the comprehension and management of ambiguity. Both cognitive structures play essential roles in navigating uncertainty. These results underscore the importance of IC and SC in effective decision-making. The findings suggest that fostering these cognitive abilities may improve decision-making skills in uncertain contexts, offering practical implications for training and development in high-stakes environments.